Effect of DC link capacitor short-circuit on an inverter fed induction motor performance - Oudaa, Cheikh; Mahmoud, Ethmane Isselem Arbih; Khelif, Mohamed Amine; Yahya, Ahmed Mohamed; Azeddine, Bendiabdellah; Mahmoud, Abdel Kader (International Journal of Applied Power Engineering (IJAPE), 2025)
Induction motors are widely used in industrial power plants because of their durability, reliability and high performance under different operating conditions of the electrical system. It is also important to note that most of these motors are controlled by variable frequency drives. By adjusting the drive parameters, the motor can be managed according to design. The reliability of motor control systems based on variable speed drives is therefore crucial for industrial applications. Unlike induction motors, the power supply components of these electrical machines are delicate and susceptible to faults. To enhance the performance of the control-motor system, it is essential for researchers to understand how faults affect the drive system as a whole. In this context, this paper addresses short-circuit faults in the intermediate circuit capacitor of an induction motor driven by an inverter. The simulation results of these capacitors faults are presented, and their impact on the behavior of the rectifier, the inverter, and the induction motor is analyzed and interpreted.